A review on nanostructured silver as a basic ingredient in medicine: physicochemical parameters and characterization - Misirli, Gabriel M.; Sridharan, Kishore; Abrantes, Shirley M. P. (Beilstein Journal of Nanotechnology, 2021)
Recent studies with silver nanoparticles (AgNPs) and the history of silver metal as a broad-spectrum bactericidal and virucidal agent, places silver as one of the future biocidal candidates in the field of nanomedicine to eliminate bacteria and viruses, especially multidrug resistant ones. In this review, we have described the various morphologies of AgNPs and correlated the enhanced bactericidal activity with their prominent {111} facets. In addition to prioritizing the characterization we have also discussed the importance of quantifying AgNPs and silver ion content (Ag+) and their different mechanisms at the chemical, biological, pharmacological, and toxicological levels. The mechanism of action of AgNPs against various bacteria and viruses including the SARS-CoV-2 was analyzed in order to understand its effectiveness as an antimicrobial agent with therapeutic efficacy and low toxicity. Further, there is the need to characterize AgNPs and quantify the content of free Ag+ for the implementation of new systematic studies of this promising agent in nanomedicine and in clinical practice.
Keywords: bactericidal agent; {111} facets; mechanism of action; silver ion; silver nanoparticles; quality control; virucidal agent

Progress in Medicinal Chemistry - Russell, A. D.; Hugo, W. B. (7 Antimicrobial Activity and Action of Silver, 1994)

(untitled) - Singh, M.; Singh, S.; Prasad, S.; Gambhir, I. S. (Dig. J. Nanomater. Biostructures, 2008)

Aristotle: A Very Short Introduction - Barnes, J. (Oxford University Press, 2000)

(untitled) - Chambers, C. W.; Proctor, C. M.; Kabler, P. W. (J. - Am. Water Works Assoc., 1962)

(untitled) - Morones, R. R. (Rev. Digit. Univ., 2009)

(untitled) - Mei, L.; Lu, Z.; Zhang, W.; Wu, Z.; Zhang, X.; Wang, Y.; Luo, Y.; Li, C.; Jia, Y. (Biomaterials, 2013)

(untitled) - Chen, M.; Yang, Z.; Wu, H.; Pan, X.; Xie, X.; Wu, C. (Int. J. Nanomed., 2011)

(untitled) - Morones, J. R.; Elechiguerra, J. L.; Camacho, A.; Holt, K.; Kouri, J. B.; Ramírez, J. T.; Yacaman, M. J. (Nanotechnology, 2005)

(untitled) - Park, H.-J.; Kim, J. Y.; Kim, J.; Lee, J.-H.; Hahn, J.-S.; Gu, M. B.; Yoon, J. (Water Res., 2009)

(untitled) - Levard, C.; Hotze, E. M.; Lowry, G. V.; Brown, G. E., Jr (Environ. Sci. Technol., 2012)

(untitled) - Gordon, O.; Vig Slenters, T.; Brunetto, P. S.; Villaruz, A. E.; Sturdevant, D. E.; Otto, M.; Landmann, R.; Fromm, K. M. (Antimicrob. Agents Chemother., 2010)

(untitled) - Matsumura, Y.; Yoshikata, K.; Kunisaki, S.-i.; Tsuchido, T. (Appl. Environ. Microbiol., 2003)

(untitled) - Foldbjerg, R.; Dang, D. A.; Autrup, H. (Arch. Toxicol., 2011)

(untitled) - Park, E.-J.; Yi, J.; Kim, Y.; Choi, K.; Park, K. (Toxicol. In Vitro, 2010)

Silver Nanoparticles - Klippstein, R.; Fernandez-Montesinos, R.; Castillo, P. M.; Zaderenko, A. P.; Pozo, D. (Silver Nanoparticles Interactions with the Immune System: Implications for Health and Disease, 2010)

(untitled) - Geissen, V.; Mol, H.; Klumpp, E.; Umlauf, G.; Nadal, M.; van der Ploeg, M.; van de Zee, S. E. A. T. M.; Ritsema, C. J. (Int. Soil Water Conserv. Res., 2015)

(untitled) - Sridharan, K.; Shenoy, S.; Kumar, S. G.; Terashima, C.; Fujishima, A.; Pitchaimuthu, S. (Catalysts, 2021)

Prioritization of Pathogens to Guide Discovery, Research and Development of New Antibiotics for Drug Resistant Bacterial Infections, Including Tuberculosis - WHO (2017)

(untitled) - Laxminarayan, R.; Duse, A.; Wattal, C.; Zaidi, A. K. M.; Wertheim, H. F. L.; Sumpradit, N.; Vlieghe, E.; Hara, G. L.; Gould, I. M.; Goossens, H.; Greko, C.; So, A. D.; et al. (Lancet Infect. Dis., 2013)

(untitled) - Barker, K. F. (Br. J. Clin. Pharmacol., 2001)

(untitled) - Stewart, P. S.; William Costerton, J. (Lancet, 2001)

No Time to Wait - WHO (2019)

(untitled) - Markowska, K.; Grudniak, A. M.; Wolska, K. I. (Acta Biochim. Pol., 2013)

(untitled) - Martinez-Gutierrez, F.; Boegli, L.; Agostinho, A.; Sánchez, E. M.; Bach, H.; Ruiz, F.; James, G. (Biofouling, 2013)

(untitled) - Pareek, V.; Gupta, R.; Panwar, J. (Mater. Sci. Eng., C, 2018)

(untitled) - Jain, J.; Arora, S.; Rajwade, J. M.; Omray, P.; Khandelwal, S.; Paknikar, K. M. (Mol. Pharmaceutics, 2009)

(untitled) - Mathur, P.; Jha, S.; Ramteke, S.; Jain, N. K. (Artif. Cells, Nanomed., Biotechnol., 2018)

(untitled) - Lara, H. H.; Ayala-Núñez, N. V.; del Carmen Ixtepan Turrent, L.; Rodríguez Padilla, C. (World J. Microbiol. Biotechnol., 2010)

(untitled) - Pal, S.; Tak, Y. K.; Song, J. M. (Appl. Environ. Microbiol., 2007)

(untitled) - Ghosh, S.; Patil, S.; Ahire, M.; Kitture, R.; Kale, S.; Pardesi, K.; Cameotra, S. S.; Bellare, J.; Dhavale, D. D.; Jabgunde, A.; Chopade, B. A. (Int. J. Nanomed., 2012)

(untitled) - Markowska, K.; Grudniak, A. M.; Milczarek, B.; Wolska, K. I. (Pol. J. Microbiol., 2018)

(untitled) - Morones-Ramirez, J. R.; Gallegos-López, S. (Cienc. Desarrollo, 2014)

(untitled) - Zhang, X.-F.; Liu, Z.-G.; Shen, W.; Gurunathan, S. (Int. J. Mol. Sci., 2016)

(untitled) - Jortner, J. (Z. Phys. D: At., Mol. Clusters, 1992)

(untitled) - Roduner, E. (Chem. Soc. Rev., 2006)

(untitled) - Wang, Z. L. (J. Phys. Chem. B, 2000)

(untitled) - Wiley, B. J.; Xiong, Y.; Li, Z.-Y.; Yin, Y.; Xia, Y. (Nano Lett., 2006)

(untitled) - Wiley, B.; Sun, Y.; Xia, Y. (Langmuir, 2005)

(untitled) - McLellan, J. M.; Siekkinen, A.; Chen, J.; Xia, Y. (Chem. Phys. Lett., 2006)

(untitled) - Bastys, V.; Pastoriza-Santos, I.; Rodríguez-González, B.; Vaisnoras, R.; Liz-Marzán, L. M. (Adv. Funct. Mater., 2006)

(untitled) - Jiu, J.; Murai, K.; Kim, D.; Kim, K.; Suganuma, K. (Mater. Chem. Phys., 2009)

(untitled) - Sridharan, K.; Endo, T.; Cho, S.-G.; Kim, J.; Park, T. J.; Philip, R. (Opt. Mater. (Amsterdam, Neth.), 2013)

(untitled) - Agnihotri, S.; Mukherji, S.; Mukherji, S. (RSC Adv., 2014)

(untitled) - Ajayan, P. M.; Marks, L. D. (Phys. Rev. Lett., 1988)

(untitled) - Van Dong, P.; Ha, C. H.; Binh, L. T.; Kasbohm, J. (Int. Nano Lett., 2012)

(untitled) - Acharya, D.; Singha, K. M.; Pandey, P.; Mohanta, B.; Rajkumari, J.; Singha, L. P. (Sci. Rep., 2018)

(untitled) - Wang, M.; Liang, Y.; Zhang, Z.; Ren, G.; Liu, Y.; Wu, S.; Shen, J. (Anal. Chim. Acta, 2019)

Biomedical Application of Nanoparticles - Rihn, B. H. (CRC Press/Taylor & Francis Group, 2018)

(untitled) - Thomas, A.; Torres Tapia, E. C.; Ramirez, A. (J. Nanocs. Moletrón, 2015)

Silver Nanoparticles for Antibacterial Devices - Meng, E.; Zhang, Q.; Li, F.; Peretyazhko, T. S. (Dissolution of Silver Nanoparticles, 2017)

(untitled) - Peretyazhko, T. S.; Zhang, Q.; Colvin, V. L. (Environ. Sci. Technol., 2014)

(untitled) - Grillet, N.; Manchon, D.; Cottancin, E.; Bertorelle, F.; Bonnet, C.; Broyer, M.; Lermé, J.; Pellarin, M. (J. Phys. Chem. C, 2013)

(untitled) - Sharma, V. K.; Siskova, K. M.; Zboril, R.; Gardea-Torresdey, J. L. (Adv. Colloid Interface Sci., 2014)

(untitled) - Kittler, S.; Greulich, C.; Diendorf, J.; Köller, M.; Epple, M. (Chem. Mater., 2010)

(untitled) - Liu, J.; Hurt, R. H. (Environ. Sci. Technol., 2010)

(untitled) - Zhang, W.; Yao, Y.; Sullivan, N.; Chen, Y. (Environ. Sci. Technol., 2011)

(untitled) - Molleman, B.; Hiemstra, T. (Langmuir, 2015)

Réponse optique de nano-objets uniques d’argent : couplage plasmonique et photooxidation - Grillet, N. (Université Claude Bernard - Lyon I, 2011)

(untitled) - Liu, J.; Wang, Z.; Liu, F. D.; Kane, A. B.; Hurt, R. H. (ACS Nano, 2012)

(untitled) - Sadeghi, B.; Garmaroudi, F. S.; Hashemi, M.; Nezhad, H. R.; Nasrollahi, A.; Ardalan, S.; Ardalan, S. (Adv. Powder Technol., 2012)

(untitled) - Kalfagiannis, N.; Karagiannidis, P. G.; Pitsalidis, C.; Panagiotopoulos, N. T.; Gravalidis, C.; Kassavetis, S.; Patsalas, P.; Logothetidis, S. (Sol. Energy Mater. Sol. Cells, 2012)

(untitled) - Halas, N. J.; Lal, S.; Chang, W.-S.; Link, S.; Nordlander, P. (Chem. Rev., 2011)

(untitled) - Wiley, B. J.; Im, S. H.; Li, Z.-Y.; McLellan, J.; Siekkinen, A.; Xia, Y. (J. Phys. Chem. B, 2006)

(untitled) - Pines, D. (Rev. Mod. Phys., 1956)

(untitled) - Stamplecoskie, K. G.; Scaiano, J. C. (J. Am. Chem. Soc., 2010)

(untitled) - Mie, G. (Ann. Phys. (Berlin, Ger.), 1908)

(untitled) - Alshareef, A.; Laird, K.; Cross, R. B. M. (Appl. Surf. Sci., 2017)

(untitled) - Rai, M. K.; Deshmukh, S. D.; Ingle, A. P.; Gade, A. K. (J. Appl. Microbiol., 2012)

The Body Eletric: Electromagnetism and the Foundation of Life - Becker, R. O.; Selden, G. (HarperCollins Publishers Inc, 1998)

(untitled) - Monowar, T.; Rahman, M.; Bhore, S.; Raju, G.; Sathasivam, K. (Molecules, 2018)

(untitled) - Das, B.; Dash, S. K.; Mandal, D.; Ghosh, T.; Chattopadhyay, S.; Tripathy, S.; Das, S.; Dey, S. K.; Das, D.; Roy, S. (Arabian J. Chem., 2017)

(untitled) - Hwang, I.; Lee, J.; Hwang, J. H.; Kim, K.-J.; Lee, D. G. (FEBS J., 2012)

Anais do IV International Symposium on Immunobiological e VII Seminário Anual Científico e Tecnológico de Bio-Manguinhos - Figueiredo, A.; Misirli, G.; Rodrigues, M.; Conte, F. (Synergistic effect between silver nanoparticles and amphotericin B on pathogenic fungi, 2019)

(untitled) - Bocate, K. P.; Reis, G. F.; de Souza, P. C.; Oliveira Junior, A. G.; Durán, N.; Nakazato, G.; Furlaneto, M. C.; de Almeida, R. S.; Panagio, L. A. (Int. J. Food Microbiol., 2019)

(untitled) - Galdiero, S.; Falanga, A.; Vitiello, M.; Cantisani, M.; Marra, V.; Galdiero, M. (Molecules, 2011)

(untitled) - Du, T.; Liang, J.; Dong, N.; Lu, J.; Fu, Y.; Fang, L.; Xiao, S.; Han, H. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Jeremiah, S. S.; Miyakawa, K.; Morita, T.; Yamaoka, Y.; Ryo, A. (Biochem. Biophys. Res. Commun., 2020)

(untitled) - Wong, K. K. Y.; Cheung, S. O. F.; Huang, L.; Niu, J.; Tao, C.; Ho, C.-M.; Che, C.-M.; Tam, P. K. H. (ChemMedChem, 2009)

(untitled) - Hebeish, A.; El-Rafie, M. H.; EL-Sheikh, M. A.; Seleem, A. A.; El-Naggar, M. E. (Int. J. Biol. Macromol., 2014)

(untitled) - Mohamed El-Rafie, H.; Abdel-Aziz Hamed, M. (Adv. Nat. Sci.: Nanosci. Nanotechnol., 2014)

(untitled) - Sabaratnam, V.; Gurunathan, S.; Raman, J.; Abd Malek, S. N.; John, P. (Int. J. Nanomed., 2013)

(untitled) - Gurunathan, S.; Lee, K.-J.; Kalishwaralal, K.; Sheikpranbabu, S.; Vaidyanathan, R.; Eom, S. H. (Biomaterials, 2009)

(untitled) - Marcato, P. D.; De Paula, L. B.; Melo, P. S.; Ferreira, I. R.; Almeida, A. B. A.; Torsoni, A. S.; Alves, O. L. (J. Nanomater., 2015)

(untitled) - Rao, C. N. R.; Kulkarni, G. U.; Thomas, P. J.; Edwards, P. P. (Chem. Soc. Rev., 2000)

Doenças Negligenciadas - Valverde, R.

Metal Nanoparticles in Pharma - Durán, M.; Fávaro, W. J.; Islan, G. A.; Castro, G. R.; Durán, N. (Silver Nanoparticles for Treatment of Neglected Diseases, 2017)

(untitled) - Soni, N.; Prakash, S. (Adv. Nanopart., 2013)

(untitled) - Sujitha, V.; Murugan, K.; Paulpandi, M.; Panneerselvam, C.; Suresh, U.; Roni, M.; Nicoletti, M.; Higuchi, A.; Madhiyazhagan, P.; Subramaniam, J.; Dinesh, D.; Vadivalagan, C.; et al. (Parasitol. Res., 2015)

(untitled) - Rossi-Bergmann, B.; Pacienza-Lima, W.; Marcato, P. D.; de Conti, R.; Durán, N. (J. Nano Res., 2012)

(untitled) - Javed, B.; Raja, N. I.; Nadhman, A.; Mashwani, Z.-u.-R. (Appl. Nanosci., 2020)

(untitled) - Taher Mohammed, O.; Jamal Abdulkhaliq, R.; Taher Mohammed, S. (J. Phys.: Conf. Ser., 2019)

(untitled) - Fanti, J. R.; Tomiotto-Pellissier, F.; Miranda-Sapla, M. M.; Cataneo, A. H. D.; de Jesus Andrade, C. G. T.; Panis, C.; da Silva Rodrigues, J. H.; Wowk, P. F.; Kuczera, D.; Costa, I. N.; Nakamura, C. V.; Nakazato, G.; et al. (Acta Trop., 2018)

(untitled) - Soni, N.; Prakash, S. (Parasitol. Res., 2014)

(untitled) - Neves Borgheti-Cardoso, L.; San Anselmo, M.; Lantero, E.; Lancelot, A.; Serrano, J. L.; Hernández-Ainsa, S.; Fernàndez-Busquets, X.; Sierra, T. (J. Mater. Chem. B, 2020)

(untitled) - Borase, H. P.; Patil, C. D.; Salunkhe, R. B.; Narkhede, C. P.; Salunke, B. K.; Patil, S. V. (J. Nanomed. Biother. Discovery, 2013)

(untitled) - Neves, B. J.; Andrade, C. H.; Cravo, P. V. L. (Molecules, 2015)

(untitled) - Moustafa, M. A.; Mossalem, H. S.; Sarhan, R. M.; Abdel-Rahman, A. A.; Hassan, E. M. (Parasitol. Res., 2018)

(untitled) - Adeyemi, O. S.; Whiteley, C. G. (Biochim. Biophys. Acta, Gen. Subj., 2014)

(untitled) - Brito, T. K.; Silva Viana, R. L.; Gonçalves Moreno, C. J.; da Silva Barbosa, J.; Lopes de Sousa Júnior, F.; Campos de Medeiros, M. J.; Melo-Silveira, R. F.; Almeida-Lima, J.; de Lima Pontes, D.; Sousa Silva, M.; Oliveira Rocha, H. A. (Int. J. Nanomed., 2020)

(untitled) - Krishnaraj, C.; Harper, S. L.; Choe, H. S.; Kim, K.-P.; Yun, S.-I. (Bioprocess Biosyst. Eng., 2015)

(untitled) - Zheng, K.; Setyawati, M. I.; Leong, D. T.; Xie, J. (Coord. Chem. Rev., 2018)

(untitled) - Carlson, C.; Hussain, S. M.; Schrand, A. M.; Braydich-Stolle, L. K.; Hess, K. L.; Jones, R. L.; Schlager, J. J. (J. Phys. Chem. B, 2008)

(untitled) - AshaRani, P. V.; Low Kah Mun, G.; Hande, M. P.; Valiyaveettil, S. (ACS Nano, 2009)

(untitled) - Keyer, K.; Imlay, J. A. (Proc. Natl. Acad. Sci. U. S. A., 1996)

(untitled) - Koduru, J. R.; Kailasa, S. K.; Bhamore, J. R.; Kim, K.-H.; Dutta, T.; Vellingiri, K. (Adv. Colloid Interface Sci., 2018)

(untitled) - Wakshlak, R. B.-K.; Pedahzur, R.; Avnir, D. (Sci. Rep., 2015)

(untitled) - Gogoi, S. K.; Gopinath, P.; Paul, A.; Ramesh, A.; Ghosh, S. S.; Chattopadhyay, A. (Langmuir, 2006)

Structure and Function of Bacterial Cells - Todar, K.

(untitled) - Mori, Y.; Ono, T.; Miyahira, Y.; Nguyen, V. Q.; Matsui, T.; Ishihara, M. (Nanoscale Res. Lett., 2013)

(untitled) - Khandelwal, N.; Kaur, G.; Kumar, N.; Tiwari, A. (Dig. J. Nanomater. Biostructures, 2014)

(untitled) - Elechiguerra, J. L.; Burt, J. L.; Morones, J. R.; Camacho-Bragado, A.; Gao, X.; Lara, H. H.; Yacaman, M. J. (J. Nanobiotechnol., 2005)

(untitled) - Rogers, J. V.; Parkinson, C. V.; Choi, Y. W.; Speshock, J. L.; Hussain, S. M. (Nanoscale Res. Lett., 2008)

(untitled) - Speshock, J. L.; Murdock, R. C.; Braydich-Stolle, L. K.; Schrand, A. M.; Hussain, S. M. (J. Nanobiotechnol., 2010)

(untitled) - Fensterl, V.; Sen, G. C. (J. Virol., 2015)

(untitled) - Castillo, P. M.; Herrera, J. L.; Fernandez-Montesinos, R.; Caro, C.; Zaderenko, A. P.; Mejías, J. A.; Pozo, D. (Nanomedicine (London, U. K.), 2008)

(untitled) - Luo, Y.-H.; Chang, L. W.; Lin, P. (BioMed Res. Int., 2015)

(untitled) - Morris, D.; Ansar, M.; Speshock, J.; Ivanciuc, T.; Qu, Y.; Casola, A.; Garofalo, R. (Viruses, 2019)

(untitled) - Baram-Pinto, D.; Shukla, S.; Perkas, N.; Gedanken, A.; Sarid, R. (Bioconjugate Chem., 2009)

(untitled) - Xiang, D.; Zheng, Y.; Duan, W.; Li, X.; Yin, J.; Shigdar, S.; O’Conner, M. L.; Marappan, M.; Zhao, X.; Miao, Y.; Xiang, B.; Zheng, C. (Int. J. Nanomed., 2013)

(untitled) - Balagna, C.; Perero, S.; Percivalle, E.; Nepita, E. V.; Ferraris, M. (Open Ceram., 2020)

(untitled) - Neagu, M.; Piperigkou, Z.; Karamanou, K.; Engin, A. B.; Docea, A. O.; Constantin, C.; Negrei, C.; Nikitovic, D.; Tsatsakis, A. (Arch. Toxicol., 2017)

(untitled) - Liu, W.; Worms, I. A. M.; Herlin-Boime, N.; Truffier-Boutry, D.; Michaud-Soret, I.; Mintz, E.; Vidaud, C.; Rollin-Genetet, F. (Nanoscale, 2017)

(untitled) - Huang, H.; Lai, W.; Cui, M.; Liang, L.; Lin, Y.; Fang, Q.; Liu, Y.; Xie, L. (Sci. Rep., 2016)

(untitled) - Shannahan, J. H.; Podila, R.; Aldossari, A. A.; Emerson, H.; Powell, B. A.; Ke, P. C.; Rao, A. M.; Brown, J. M. (Toxicol. Sci., 2015)

(untitled) - Silva, A. L.; Peres, C.; Conniot, J.; Matos, A. I.; Moura, L.; Carreira, B.; Sainz, V.; Scomparin, A.; Satchi-Fainaro, R.; Préat, V.; Florindo, H. F. (Semin. Immunol., 2017)

(untitled) - Dacoba, T. G.; Olivera, A.; Torres, D.; Crecente-Campo, J.; Alonso, M. J. (Semin. Immunol., 2017)

(untitled) - Greulich, C.; Braun, D.; Peetsch, A.; Diendorf, J.; Siebers, B.; Epple, M.; Köller, M. (RSC Adv., 2012)

(untitled) - Melo, P. S.; Marcato, P. D.; Huber, S. C.; Ferreira, I. R.; de Paula, L. B.; Almeida, A. B. A.; Durán, N.; Torsoni, S.; Seabra, A. B.; Alves, O. L. (J. Phys.: Conf. Ser., 2011)

(untitled) - Korani, M.; Ghazizadeh, E.; Korani, S.; Hami, Z.; Mohammadi-Bardbori, A. (Eur. J. Nanomed., 2015)

(untitled) - Munger, M. A.; Radwanski, P.; Hadlock, G. C.; Stoddard, G.; Shaaban, A.; Falconer, J.; Grainger, D. W.; Deering-Rice, C. E. (Nanomedicine (N. Y., NY, U. S.), 2014)

Nano Silver - NICNAS Nanomaterial health hazard review: health effects of silver nanoparticles - NICNAS

(untitled) - Piao, M. J.; Kim, K. C.; Choi, J.-Y.; Choi, J.; Hyun, J. W. (Toxicol. Lett., 2011)

(untitled) - Mosmann, T. (J. Immunol. Methods, 1983)

(untitled) - Kumar, P.; Nagarajan, A.; Uchil, P. D. (Cold Spring Harb. Protoc., 2018)

(untitled) - Liu, J.-f.; Yu, S.-j.; Yin, Y.-g.; Chao, J.-b. (TrAC, Trends Anal. Chem., 2012)

(untitled) - Cushing, B. L.; Kolesnichenko, V. L.; O'Connor, C. J. (Chem. Rev., 2004)

(untitled) - Pillai, Z. S.; Kamat, P. V. (J. Phys. Chem. B, 2004)

(untitled) - Turkevich, J.; Stevenson, P. C.; Hillier, J. (Discuss. Faraday Soc., 1951)

(untitled) - Wiley, B.; Sun, Y.; Mayers, B.; Xia, Y. (Chem. – Eur. J., 2005)

(untitled) - Fievet, F.; Lagier, J. P.; Blin, B.; Beaudoin, B.; Figlarz, M. (Solid State Ionics, 1989)

Silver Nanoparticle Applications - Pacioni, N. L.; Borsarelli, C. D.; Rey, V.; Veglia, A. V. (Synthetic Routes for the Preparation of Silver Nanoparticles, 2015)

(untitled) - Im, S. H.; Lee, Y. T.; Wiley, B.; Xia, Y. (Angew. Chem., Int. Ed., 2005)

(untitled) - Chang, S.; Chen, K.; Hua, Q.; Ma, Y.; Huang, W. (J. Phys. Chem. C, 2011)

(untitled) - Liang, H.; Wang, W.; Huang, Y.; Zhang, S.; Wei, H.; Xu, H. (J. Phys. Chem. C, 2010)

(untitled) - Kim, D.; Jeong, S.; Moon, J. (Nanotechnology, 2006)

(untitled) - Durán, N.; Rolim, W.; Durán, M.; Fávaro, W.; Seabra, A. (Quim. Nova, 2018)

(untitled) - Weinberg, H.; Galyean, A.; Leopold, M. (TrAC, Trends Anal. Chem., 2011)

(untitled) - Goto, K.; Taguchi, S.; Fukue, Y.; Ohta, K.; Watanabe, H. (Talanta, 1977)

(untitled) - Hinze, W. L.; Pramauro, E. (Crit. Rev. Anal. Chem., 1993)

IUPAC Compendium of Chemical Terminology - BIPM (B. international des poids et mesures. Avogadro Constant, 2019)

(untitled) - Zhang, Q.; Li, N.; Goebl, J.; Lu, Z.; Yin, Y. (J. Am. Chem. Soc., 2011)

(untitled) - Moores, A.; Goettmann, F. (New J. Chem., 2006)

(untitled) - Bhattacharjee, S. (J. Controlled Release, 2016)

(untitled) - Fan, X.; Zheng, W.; Singh, D. J. (Light: Sci. Appl., 2014)

(untitled) - Danaei, M.; Dehghankhold, M.; Ataei, S.; Hasanzadeh Davarani, F.; Javanmard, R.; Dokhani, A.; Khorasani, S.; Mozafari, M. R. (Pharmaceutics, 2018)

(untitled) - Lin, P.-C.; Lin, S.; Wang, P. C.; Sridhar, R. (Biotechnol. Adv., 2014)

(untitled) - Bragg, P. W. H.; Bragg, W. L. (Proc. R. Soc. London, Ser. A, 1913)

Silver Nanoparticles - Fabrication, Characterization and Applications - Chouhan, N. (Silver Nanoparticles: Synthesis, Characterization and Applications, 2018)

(untitled) - Macaluso, R. T. (ACS Symp. Ser., 2010)

(untitled) - Paranhos, C. M.; Soares, B. G.; Machado, J. C.; Windmöller, D.; Pessan, L. A. (Eur. Polym. J., 2007)